2020
DOI: 10.1177/0885066620905796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Ultrasonography in Neurocritically Ill Patients

Abstract: Ultrasonography is part of the multimodal monitoring of the neurocritical patient. Through transcranial color Doppler ultrasound, carotid-color Doppler ultrasound, and ocular ultrasound it is possible to diagnose and monitor a multitude of pathological conditions, such as cerebrovascular events, vasospasm, Terson syndrome, carotid atheromatosis, and brain death. Furthermore, these techniques enable the monitoring of the intracranial pressure, the cerebral perfusion pressure, and the midline deviation, which al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Nowadays, assessment of CBF using TCD is being performed when facing rapid neurological changes following extra-dural or subarachnoid hematomas or even after cerebral aneurysm rupture [14,15]. Nevertheless, studies have demonstrated a good correla-tion between changes in CBF using NIRS and those measured by TCD.…”
Section: A a B Bmentioning
confidence: 99%
“…Nowadays, assessment of CBF using TCD is being performed when facing rapid neurological changes following extra-dural or subarachnoid hematomas or even after cerebral aneurysm rupture [14,15]. Nevertheless, studies have demonstrated a good correla-tion between changes in CBF using NIRS and those measured by TCD.…”
Section: A a B Bmentioning
confidence: 99%
“…The relatively lower thickness of the skull around pterion, and the temporal bones adjacent to the ears—the temporal window—lets the ultrasound beam through and allows visualisation of the anatomy near circle of Willis 5 6. While many of the intracranial arteries can be studied, this article will focus on the MCA, because its size, position, direction of blood flow and significance make it the ideal candidate vessel to be insonated.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound probe is placed so the beam is directed towards the opposite ear, whereas the probe marker faces anteriorly. Adapted from Caballero-Lozada et al 6 MCA, middle cerebral artery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can detect most lesions requiring interventional therapy, such as angioplasty, stenting, and local thrombolysis [3]. It can assess the cerebral hemodynamic consequences of steno-occlusive lesions in the cervical parent artery and monitor Intracranial Pressure (ICP), Cerebral Perfusion Pressure (CPP), and Midline Deviation allowing us to assess the patient's neurocritical pathological characteristics in a non-invasive manner [4].…”
Section: Introductionmentioning
confidence: 99%